Effects of Science, Technology, Engineering, and Mathematics Education Using Algodoo to Prospective Science Teachers' Scientific Process and Education Orientation Skills - Alan, Burcu; Zengin, Fikriye K.; Kececi, Gonca (Sage Publications Inc, 2023)
This study investigated the effects of science, technology, engineering, and mathematics (STEM) applications carried out with the purpose of supporting the integrated knowledge of prospective science teachers on the scientific process skills and STEM education orientation skills of prospective teachers. According to the results, the STEM application was effective on the scientific process skills of the prospective teachers in the experiment group in comparison to those in the control group; however, it was not effective on their levels of orientation towards STEM education. The prospective teachers stated that Algodoo is a good tool for integration of STEM disciplines.
Keywords: Science; technology; engineering; mathematics education; integrated teaching knowledge; prospective science teachers; Algodoo software